The secondary structure of guide RNA molecules from Trypanosoma brucei. - Schmid, B (1995)
RNA editing in kinetoplastid organisms is a mitochondrial RNA processing phenomenon that is characterized by the insertion and deletion of uridine nucleotides into incomplete mRNAs. Key molecules in the process are guide RNAs which direct the editing reaction by virtue of their primary sequences in an RNA-RNA interaction with the pre-edited mRNAs. To understand the molecular details of this reaction, especially potential RNA folding and unfolding processes as well as assembly phenomena with mitochondrial proteins, we analyzed the secondary structure of four different guide RNAs from Trypanosoma brucei at physiological conditions. By using structure-sensitive chemical and enzymatic probes in combination with spectroscopic techniques we found that the four molecules despite their different primary sequences, fold into similar structures consisting of two imperfect hairpin loops of low thermodynamic stability. The molecules melt in two-state monomolecular transitions with Tms between 33 and 39 degrees C and transition enthalpies of -32 to -38 kcal/mol. Both terminal ends of the RNAs are single-stranded with the 3' ends possibly adopting a single-stranded, helical conformation. Thus, it appears that the gRNA structures are fine tuned to minimize stability for an optimal annealing reaction to the pre-mRNAs while at the same time maximizing higher order structural features to permit the assembly with other mitochondrial components into the editing machinery.